Meningkatkan Kemampuan Berhitung MelaluiPermainan Kartu Angka Pada Anak Di RA AlBasithiyah Batu Tunggal - Ernawati; Suryatik; Ismi Yulizar; Soybatul Aslamiah Ritonga (Jurnal Zeniusi, 2024)
This research is based on child development in Raudhatul Athfal Al-Bashitiyah. In learning activities in early childhood education RA Al-Basithiyah in group B, the ability to recognize children's numbers is still very low. When asked to show numbers and match the shape of the numbers. In addition, there are only 13 children who can write numbers 1-10, and only 17 can re-state numbers 1-10 in sequence. The reason for the inability of children in RA Al-Basithiyah to recognize and mention the concept of numbers 1-10 is that the learning method used in recognizing numbers is not optimal. Very minimal learning media is used to recognize numbers, so it cannot stimulate children to recognize them. This study aims to determine whether using number card media can improve children's counting skills in RA Al Bashitiyah. This research is Classroom Action Research (CAR). Data collection techniques in this study were observation and documentation. The subjects in thisstudy were children of RA Al Bashitiyah. The results of this study used two cycles: in cycle I, the MB category had 18 children (60%) and BSH 12 children (40%). In cycle II, the MB category was two children (7%), and the BSB category was 28 children (93%), meaning cycle II was declared complete. It can be concluded that number card games can improve children's counting skills.